Symposium 8: Learning in the Extended University: An Overview - Booth, Shirley (Proceedings of the International Conference on Networked Learning, 2006)
A research project is to be presented in this symposium, organized according to three component studies. All relate to learning in networked learning situations, which can be characterized as extending the university outside its normal field of educational activity in several respects. This overview is concerned mostly with setting the scene in terms of the background to the project and the research approaches we are adopting and adapting. The remaining three papers take up aspects of the individual studies.